Pahangs UMP now known as UMPSA - T.N., Alagesh (New Straits Times Press (M) Bhd., 2023)
PEKAN: Universiti Malaysia Pahang (UMP), which marked its 21st anniversary in February this year, is now known as Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).